2021
DOI: 10.3390/ijms22168558
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of the In Vitro Cytokinesis-Block Micronucleus Test for Genotoxicity Assessment of TiO2 Nanoparticles on SH-SY5Y Cells

Abstract: Standard toxicity tests might not be fully adequate for evaluating nanomaterials since their unique features are also responsible for unexpected interactions. The in vitro cytokinesis-block micronucleus (CBMN) test is recommended for genotoxicity testing, but cytochalasin-B (Cyt-B) may interfere with nanoparticles (NP), leading to inaccurate results. Our objective was to determine whether Cyt-B could interfere with MN induction by TiO2 NP in human SH-SY5Y cells, as assessed by CBMN test. Cells were treated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Cytochalasin B has been shown to interfere with actin filaments required for endocytosis and thus co-exposures should be avoided; this recommendation have been extensively outlined in previous publications [ 1 , 5 , 42 ]. Recently, Fernandez-Bertolez (2022) have reported that cellular uptake of TiO 2 ENPs and micronucleus induction is not affected by the presence or absence of cyto B during the exposure period in SH-SY5Y cells [ 43 ]. This could indicate that in some cells other modes of nanomaterial uptake is present.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochalasin B has been shown to interfere with actin filaments required for endocytosis and thus co-exposures should be avoided; this recommendation have been extensively outlined in previous publications [ 1 , 5 , 42 ]. Recently, Fernandez-Bertolez (2022) have reported that cellular uptake of TiO 2 ENPs and micronucleus induction is not affected by the presence or absence of cyto B during the exposure period in SH-SY5Y cells [ 43 ]. This could indicate that in some cells other modes of nanomaterial uptake is present.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, and considering the existing evidence that cytochalasin-B, used in in vitro cytokinesis-block micronucleus (CBMN), affects the uptake of nanomaterials, hindering its use in the genotoxicity testing of nanomaterials. Fernández-Bertólez et al [20] tested TiO 2 NP uptake and induced genotoxicity in neuroblastoma (SH-SY5Y) cells using flow cytometry and CBMN, after three different treatment options with cytochalasin-B, as recommended by the Organisation for Economic Co-operation and Development (OECD). The results showed that, even though there was no interference of cytochalasin-B in the uptake, micronuclei induction was affected by the presence of cytochalasin-B in the medium, possibly causing false positive results.…”
mentioning
confidence: 99%